Bromate reduction by Shewanella oneidensis MR-1 is mediated by dimethylsulfoxide reductase - Wang, Yicheng; Fan, Jiale; Shen, Yonglin; Ye, Fan; Feng, Zhiying; Yang, Qianning; Wang, Dan; Cai, Xunchao; Mao, Yanping (Frontiers in Microbiology, 2022)
Microbial bromate reduction plays an important role in remediating bromate-contaminated waters as well as biogeochemical cycling of bromine. However, little is known about the molecular mechanism of microbial bromate reduction so far. Since the model strain Shewanella oneidensis MR-1 is capable of reducing a variety of oxyanions, such as iodate, which shares a high similarity to bromate, we hypothesize that S. oneidensis MR-1 can reduce bromate. Here, we conducted an experiment to investigate whether S. oneidensis MR-1 can reduce bromate and report the bromate reduction mediated by a dimethylsulfoxide reductase encoded with dmsA. S. oneidensis MR-1 is not a bromate-respiring bacterium but can reduce bromate to bromide under microaerobic conditions. When exposed to 0.15 mM, 0.20 mM, 0.25 mM, 0.50 mM, and 1.00 mM bromate, S. oneidensis MR-1 reduced bromate by around 100%, 75%, 64%, 48%, and 23% within 12 h, respectively. In vivo evidence from gene deletion mutants and complemented strains of S. oneidensis MR-1 indicates that MtrB, MtrC, CymA, GspD, and DmsA are involved in bromate reduction, but not NapA, FccA, or SYE4. Based on our results as well as previous findings, a proposed molecular mechanism for bromate reduction is presented in this study. Moreover, genomic survey indicates that 9 of the other 56 reported Shewanella species encode proteins highly homologous to CymA, GspD and DmsA of S. oneidensis MR-1 by sequence alignment. The results of this study contribute to understanding a pathway for microbial bromate reduction.